Stieltjes and inverse Stieltjes holomorphic families of linear relations and their representations - Arlinskiĭ, Yury; Hassi, Seppo (Polish Academy of Sciences, Institute of Mathematics, 2019)
We study analytic and geometric properties of Stieltjes and inverse Stieltjes families defined on a separable Hilbert space and establish various minimal representations for them by means of compressed resolvents of various types of linear relations. Also attention is paid to some new peculiar properties of Stieltjes and inverse Stieltjes families, including an analog for the notion of inner functions which will be characterized in an explicit manner. In addition, families which admit different types of scale invariance properties are described. Two transformers that naturally appear in the Stieltjes and inverse Stieltjes classes are introduced and their fixed points are identified.
10.4064/sm180714-12-3
Keywords: Matematiikka